A Novel Index in Hepatocellular Carcinoma Patients After Curative Hepatectomy: Albumin to Gamma-Glutamyltransferase Ratio (AGR) - Shen, Junyi; Tang, Li; Zhang, Xiaoyun; Peng, Wei; Wen, Tianfu; Li, Chuan; Yang, Jiayin; Liu, Guanjian (Frontiers in Oncology, 2019)
Aim: As high gamma-glutamyltransferase level or low albumin had negative impact on the prognosis of hepatocellular carcinoma (HCC), the prognostic role of albumin to gamma-glutamyltransferase ratio (AGR) in hepatocellular carcinoma patients underwent hepatectomy remains unclear. Methods: Between January 2007 and December 2015, 1143 HCC patients after hepatectomy were reviewed from a prospectively maintained database in West China Hospital. All qualified patients(n=959) were classified as training set (year 2007-2012, n=480) and validation set (year 2012-2017, n=479). Time‐dependent receiver operating characteristic (ROC) curve analysis was performed to evaluate the performance. Result: AGR=0.5 was identified as the best cut-off point to predict recurrence free survival (RFS) and overall survival (OS) in the training set. Low AGR related to poor tumor characteristics and high systemic inflammation. Based on the multivariate analysis, high AGR was independent predictor for better RFS and OS with hazard ratio of 0.696(p=0.002) and 0.673(p=0.007). The high AGR group had better RFS and OS in training set and validation set than low AGR group. the AGR-based score (AGR-PLR) could stratify HCC patients into three subgroups with different prognosis in the training and validation set. Patients with score 1 had worse prognosis than those with AGR-PLR score 0, but better than those with AGR-PLR score 2. The predictive accuracy of the AGR-PLR score appeared superior to that of the AGR or PLR alone. Conclusions: we firstly reported that AGR≤0.5 was an independently prognostic factor in HCC after hepatectomy. The AGR-PLR score could further improve the discriminatory ability of prognosis.